Internet Banking in Nepal: Use and Challenges - Khatri, Jyoti Raj; Upadhyaya-Dhungel, Kshitiz (Banking Journal, 2013)
DOI: http://dx.doi.org/10.3126/bj.v3i2.8544 Banking Journal Vol.3(2) 2013 pp.57-77